PENERAPAN MODEL PEMBELAJARAN APTITUDE TREATMENT INTERACTION (ATI) UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS DITINJAU DARI KEMANDIRIAN BELAJAR PESERTA DIDIK - Himelda Melda Dewi (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2020)
The ability to understand mathematical concepts is one important component that must be mastered and developed. The result of the pre-study show that the ability to understandmathematical concepts of students of MTS ANNUR Karang Rejo is still low, this can be seen from the resultsof the ability to understand mathematical concepts of students in the academic year 2019/2020 obtained the above values ​​(KKM) with a value of ≥70 of 22 from 60 students. Researchers are interested in applying the learning model aptitude treatment interaction (ATI). The purpose of this study was to determine the effect of the aptitude treatment interaction (ATI) learning model to improve the ability to understand mathematical concepts in terms of students learning independence. This researchis a type of research Quasy Experimental Design. The instrument used to collect data is a test of the ability to understand mathematical concepts. Analysis of the data of this research is the analysis of variance of two paths with unequal cells. Based on the results of the study it can be concluded that: 1) there is an effect of the application of the learning model aptitude treatment interaction (ATI) to improve the ability to understand mathematical concepts compared to conventional learning, 2) there is an effect of increasing the ability to understand mathematical concepts that have high, medium, and low learning independence . 3) there is no interaction effect between the learning model and learning independence to improve students' mathematical concept understanding abilities.